Tetrahedrally Bonded Amorphous Carbon Films I Basics, Structure and Preparation - Schultrich, Bernd (Springer Series in Materials Science,, 2018)
This book presents the status quo of the structure, preparation, properties and applications of tetrahedrally bonded amorphous carbon (ta-C) films and compares them with related film systems. Tetrahedrally bonded amorphous carbon films (ta-C) combine some of the outstanding properties of diamond with the versatility of amorphous materials. The book compares experimental results with the predictions of theoretical analyses, condensing them to practicable rules. It is strictly application oriented, emphasizing the exceptional potential of ta-C for tribological coatings of tools and components.